Recent progress on the application of nanofluids and hybrid nanofluids in machining: a comprehensive review - Liew, Pay Jun; Kursus Othman, Maisarah; Che Sidik, Nor Azwadi; Wang, Jingsi (Springer Nature, 2022)
This paper summarises the recent progress of nanofluids and hybrid nanofluids in various machining processes including milling, turning, grinding and drilling. Thermophysical properties of nanofluid and hybrid nanofluid, such as viscosity, thermal conductivity, stability and wettability, are also discussed. Results showed that thermal conductivity and viscosity of nanofluid are strongly affected by temperature, mass volume fraction, types of nanoparticles and nanoparticle size. Thermophysical properties of hybrid nanofluids are greater than those of nanofluids and base fluids. Scientific findings also indicated that nanofluids and hybrid nanofluids outperform other cooling-lubrication techniques. The application of nanofluids and hybrid nanofluids enhances the surface finish and reduces the cutting temperature, cutting force and tool wear during machining. However, more research work is still needed to determine their applicability in practical industries, especially in the usage of hybrid nanofluid in milling and drilling processes.